Pure-water-soluble colorimetric chemosensors for highly sensitive and rapid detection of hydrogen sulfide: Applications to evaluation of on-site water quality and real-time gas sensors - Chun, Hye W.; Zheng, Jian; Lee, Eun Hye; Oh, Byeong M.; Lee, Chan Bong; Min, Jun Sik; Kim, Eunsu; Kim, Eunha; Lee, Woosung; Kim, Jong H. (Sensors and Actuators B: Chemical, 2024)
Hydrogen sulfide (H2S) has adverse effects on humans in various routes through water and air. However, the versatile detection of hydrogen sulfide (H2S) gas in various environments is still challenging. Herein, we report a highly sensitive, rapid, and selective colorimetric chemosensor (IID1) for the detection of H2S in diverse conditions including solution in pure water, thin-film, dyed-fabric, and coated silica in ambient air. The H2S-induced chemical reaction of IID1 results in significant spectral changes in UV-Vis absorption, accompanied by a discernible color change from dark red to colorless. Moreover, IID1 exhibits excellent selectivity among the competitive analytes, with a detection limit of 1.12 ppb and a rapid detection time (<10 s), which is among the highest performances reported for colorimetric H2S chemosensors. The detection mechanism is systemically investigated based on the analyses of UV-Vis absorption, NMR, and mass spectra. Utilizing the high solubility of IID1 in pure water, we successfully evaluate on-site water (river, lake, stream, reservoir, and tap water) quality with excellent accuracy. Furthermore, we demonstrate H2S detection on paper strips and face masks using the IID1. Our results suggest that IID1 is a practical sensor platform for the efficient detection of H2S in various environments.
Keywords: Colorimetric chemosensors; Film sensors; Hydrogen sulfide; Water evaluation; Water soluble probe